Students’ Responses in Learning Extensive Reading Through the Literature Circle - Suci, Trie Clara; Yanto, Elih Sutisna; Miftakh, Fauzi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
The literature circle develops into an interesting and challenging strategy that can encourage students to take an active role in reading instruction. The aim of this study is to investigate students’ responses to learning extensive reading through the literature circle. The participants of this study were four secondary students in Karawang. To gain the natural experience of the participants, the author uses phenomenological study. The dataset for this study were collected by observation, interviews, and documentation. The data collection methods for this study were observations, interviews, and documentation. The authors used thematic analysis. The results showed that using a literature circle can help students read more, make them feel more involved in group discussions, and encourage them to read more English textbooks. However, the authors found out some obstacles that students face while conducting this activity such as the lack of sufficient time to carry out this activity. in the question-and-answer session students feel less exporting text from their group of friends.